Theoretical Ab initio and Density Functional Study of the Hydrogen Bonding Nature Between the Pyridine-nitrogenic Base Pairs - Al-anber, M. J. (Journal of Scientific Research, 2012)
The pyridine interact with two nitrogenic bases (adenine and uracil) so that they may cause a significant point mutation. The results of theoretical ab initio study on the hydrogen bonding energies of pyridine with the adenine and uracil are reported. The geometries of the local minima for all suggested cases were optimized with Restricted Hartree-Fock RHF/cc-pVDZ and then density functional B3LYP/cc-pVDZ. The geometrical parameters, relative stability, interaction energies and nature of hydrogen bonding energy are reported. Also, focus on the range of the hydrogen bonding energy and the flexibility of the rotation angle in the P:A¹ base pair have been investigated. Additionally, the influence of the hydrogen bonding energy with the dihedral angle between the two planes of the adenine and the pyridine in the P:A¹ pair are studied. The pyridine with the adenine and uracil may be classified as multi-point mutation. In general, enzymes may have three mechanisms to recorrect the errors in the DNA and the RNA. Keywords: Ab initio; Density funtional theory; Mutating; Pyridine ; DNA. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.8721 J. Sci. Res. 4 (2), 419-425 (2012)